The carboxypeptidase B and carbonic anhydrase genes play a reproductive regulatory role during multiple matings in Ophraella communa - Chen, Guangmei; Gao, Xuyuan; Zhang, Yan; Ma, Chao; Ma, Weihua; Zhou, Zhongshi (Frontiers in Molecular Biosciences, 2023)
Seminal fluid proteins (SFPs) are key factors in sexual reproduction and are transferred to females during mating with sperm. SFPs have a nutritional value because they protect and activate sperm storage and release to optimize fecundity. Multiple matings promote ovipositioning in several insect species. Therefore, insects may obtain more SFP through multiple matings to maximize reproduction, but this process has not yet been clearly confirmed. Here, the relationship between multiple matings and the SFPs in Ophraella communa (Coleoptera: Chrysomelidae), a biological control agent of the common ragweed Ambrosia artemisiifolia (Asterales: Asteraceae), was studied. Multiple matings significantly increased female fecundity and ovary egg deposition. Carboxypeptidase B (OcCpb) and carbonic anhydrase (OcCa) genes were identified as putative SFP genes in O. communa and they showed strong male-biased expression. Additionally, OcCpb and OcCa expression was upregulated in the bursa copulatrix of mating females compared to that in virgin females, but their expression gradually declined after copulation. Furthermore, OcCpb and OcCa knockdown in males led to a decrease in insect fecundity compared to that in the control. The reproductive tract of females mated with dsRNA-treated males was dissected and observed and, notably, the ovaries produced significantly fewer eggs. These data suggest that OcCpb and OcCa play regulatory roles during multiple matings in O. communa.